STRATEGI ADAPTASI PETANI DALAM MENGHADAPI RENDAHNYA HARGA JUAL KELAPA SAWIT DI KECAMATAN SUNGAI BAHAR KABUPATEN MUARO JAMBI - Andini, Fiona; Muchlis, Fuad; Farida, Aulia (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
This study aims to determine the adaptation strategies of farmers in the face of low prices for oil palm in Sungai Bahar District. The data used are primary data obtained from direct interviews with respondents and secondary data obtained from literature and related institutions. The method used in this research is mixed methods. Data analysis is done by collecting data and analyzing quantitative data in the first stage, then collecting data and analyzing qualitative data in the second stage, then analyzing the overall data to then draw conclusions from the analysis of the data. The analysis methods are: (1) Data reduction; (2) Presentation of data and; (3) Drawing conclusions. The results showed that the adaptation strategies used were: (1) active strategy, becoming an oil palm farm laborer, opening a side business; (2) a passive strategy, utilizing home yards to grow horticultural crops, raising / raising chickens; (3) network strategy, borrowing money from relatives / neighbors, borrowing money from tauke and borrowing / borrowing daily necessities at the shop / shop.